EMPLOYEE PERFORMANCE ROLE: DISCIPLINE AND LEADERSHIP - Salman Farisi; Muhammad Arif (CERED Indonesia Institute, 2021)
The purpose of this study is to identify and analyze the influence of leadership on employee performance, identify and analyze the effect of discipline on employee performance, and leadership and discipline on employee performance at the DPRD Secretariat, identify and analyze its impact. North Sumatra. The approach used in this study is an associative approach. The population of this study consisted of 132 employees of the DPRD Secretariat of North Sumatra, and 57 samples used in this study were taken from all Slovenian recipes. The data collection method in this study used a questionnaire. The data analysis technique in this study used the classical hypothesis test, multiple regression, t test, F test, and the coefficient of determination. Data processing for this study was carried out using the SPSS program (version 2.00). Partial leadership is known to have a positive and significant effect on the performance of the North Sumatra DPRD Secretariat staff. This discipline is known to have a positive and significant impact on the performance of the North Sumatra DPRD Secretariat staff. Meanwhile, leadership and discipline are known to have a significant positive effect on the performance of the North Sumatra DPRD Secretariat staff.